Sistem Pendukung Keputusan Dalam Penentuan Kinerja Tenaga Pendidik Terbaik Menerapkan Metode MOORA - Wulan, Sri; Pratiwi, Elsa; Mesran, Mesran; Desyanti, Desyanti (Bulletin of Data Science, 2022)
The performance of educators at a university is a real behavior that is displayed by each educator as the work performance produced by the educators according to their role. To be able to determine the quality of the performance of educators, it is necessary to have clear criteria, therefore it is needed a decision support system (DSS) to overcome these problems. DSS is a Multi Objective Optimization Method on The Basis of Ratio Analysis (MOORA) method that has a high degree of flexibility and easy to understand in separating the subjective part of an evaluation process into weighted criteria decisions with several attributes of decision making. This method has a degree of goal selectivity from conflicting criteria. Where the criteria can be assessed as beneficial and unfavorable (cost). So this method has a good level of selectivity in determining the highest A1 with an optimization value of 3.059